Synthesis and radiolabeling of a nitrofuran derivate with 18F for identification of areas of hypoxia in the tumor microenvironment - Araujo, Yasniel Babi (2024)
Hypoxia, one of the hallmarks of cancer, is a pathological condition referred to a relatively low (generally < 2%) oxygen content compared to normal status in a given organ, tissue, or cell type. Positron Emission Tomography (PET) is a non-invasive molecular imaging technique widely known for studying hypoxia mostly employing 2-nitroimidazole-based radiotracer probes that directly report on oxygen levels with high specificity and spatial resolution. In this regard, [18F]FMISO is the most widely used hypoxia imaging radiopharmaceutical, but its high lipophilicity causes slow tracer accumulation, slow plasma clearance, and low tumor-to-background contrast. The mechanism of action of hypoxia-specific radiotracers lies on the selective reduction of the nitroimidazole moiety under hypoxic conditions, but other nitroaromatic compounds with improved reduction capabilities in the absence of oxygen could be used. The objective of this work was to synthesize and evaluate a nitrofuran-based radiotracer probe for detection of hypoxic areas in the tumor microenvironment, (E)-1-(4-[18F]-fluorophenyl)-3-(5-nitrofuran-2-yl)prop-2-en-1-one, baptized as [18F]FNFP, and compare it with [18F]FBNA, a novel hypoxia radioligand synthetized and characterized in a previous work. Initially, precursors for [18F]-labelling and cold standards [19F]FNFP and [19F]FBNA were prepared and characterized by spectroscopic techniques, with a novel improved synthesis in the case of the latter compared to the method reported. Late-stage radiofluorination allowed the introduction of the [18F]-fluoride in a one-step reaction without azeotropic drying, obtaining both [18]FFNFP and [18]FFBNA with >99% radiochemical purity, radiochemical yields of 38,4±3% and 39,1±5% (n=3), total synthesis time of 85 and 70 minutes, and high molar activities of 41.56 GBq/μmol and 43,02 GBq/μmol, respectively. [18]FFNFP was found to be stable in Phosphate-buffered saline (PBS) and serum for up to 6 hours and more hydrophilic than [18F]FMISO (log10P=2.06), with the same partition coefficient as [18F]FBNA (log10P=1.05). PET/CT images using an MKN-45 gastric cancer tumor model in mice showed that [18F]FNFP, a chalcone derivate, is rapidly excreted by a hepato-biliary-intestinal-renal clearance with no tumor uptake. Similar to its counterparts chalcone-based radiotracers, has a rapid washout from the brain with a high uptake in this organ in the first 15 minutes after injection. Ex vivo biodistribution studies showed no interesting tumor uptake for [18F]FNFP. Different from the 2-nitroimidazole-based radiotracer [18F]FBNA, the 5-nitrofuran derivate [18F]FNFP was not nearly as effective as the former in identifying hypoxic regions in the tumor microenvironment, perhaps due to its rapid clearance.